THE ROLE OF EDUCATION FOR THE DEVELOPMENT OF RESETTLED TRIBES IN MYSORE DISTRICT - Nagendrakumar P; Santhosh Naik R (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper examines the role of education for the development of resettled tribes in Mysore district. Resettled tribes of Mysore district are socially disadvantaged groups. Government of Karnataka has implemented several programmes for the socio economic upliftment of resettled tribes of Mysore district. Even after regular policy interventions, the literacy statuses of the resettled tribes remain deficient. The number of school drop outs is increasing while the number of girl student pursing secondary education is dropping. There is a need to focus on the issues concerning modified and easier access to education and equity for resettled tribal communities. The need to high light the problems induced after the CORONA pandemic. Hence, there is a need to intervene. Earlier Majority of the resettled settlements are deprived of basic educational support including Anganawadi centres, Vidyagama and Ashraya schools. But, Government of Karnataka along with the support of the District administration has taken several measures to spread educational access to resettled tribes. Creating programmes to bring the tribal people to the mainstream of the society and promoting decent livelihood by creating economic opportunities through skill development, capacity building and conduction of training programmes needs to be focused.